2022
DOI: 10.1088/1402-4896/ac5b43
|View full text |Cite
|
Sign up to set email alerts
|

Exploring structural, electronic, optical, magnetic, and thermoelectric properties of Pt doped and Pt-Cu/Au co-doped GaN

Abstract: We present a computational research on investigating the structural, electronic, optical, magnetic, and thermoelectric properties of Pt doped and Pt-Cu/Au co-doped GaN using the Wien2k code. The PBE-GGA approximation is employed in Wien2k code using density functional theory. Study of electronic properties reveals that the d-states of Pt, Cu, and Au atoms participate actively in transferring electron from valence to conduction band and their addition as mono and co-doped formation turns the non-magnetic charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Doping is a process by which impurities are intentionally added to a material to modify its properties. In the case of TMDCs, it has been demonstrated that doping by substitution of metallic atoms or chalcogens allows for the modification of electronic and optical properties [19,20], control of conductivity and magnetization [21], improvement of catalytic properties [22], etc. The p-type (n-type) doping is the introduction of acceptor (donor) impurities.…”
Section: Introductionmentioning
confidence: 99%
“…Doping is a process by which impurities are intentionally added to a material to modify its properties. In the case of TMDCs, it has been demonstrated that doping by substitution of metallic atoms or chalcogens allows for the modification of electronic and optical properties [19,20], control of conductivity and magnetization [21], improvement of catalytic properties [22], etc. The p-type (n-type) doping is the introduction of acceptor (donor) impurities.…”
Section: Introductionmentioning
confidence: 99%